Marta González González, Funerary Epigrams of Ancient Greece: Reflections on Literature, Society and Religion - Marchand, Fabienne (Journal of Greek Archaeology, 2021)
This book aims to review funerary epigrams from the Archaic and Classical periods, and to place them in their social and religious contexts. It consists of eight chapters, followed by 16 pages of bibliography, an index of inscriptions and table of concordances, plus five pages of indices. The main monuments are illustrated with 11 plain black and white figures, which archaeologists will not find particularly useful.